2022
DOI: 10.3390/ijerph19084672
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Analysis of Lateral Asymmetry Using Hip-Knee Angular Measures in Soccer Players: A New Methodological Perspective of Assessment for Lower Limb Asymmetry

Abstract: This study aimed to: (1) determine the magnitude and direction of lateral asymmetry in well-trained soccer players using hip and knee ROM tests; (2) inquire if asymmetry relies on the ROM test performed and/or gender; and (3) establish asymmetry thresholds for each ROM test to individualize lower-limbs asymmetry. One hundred amateur soccer players were assessed using hip–knee ROM tests: Straight Leg Raise, modified Thomas Test, hip internal rotation and external rotation, hip abduction (ABD) and adduction (ADD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Another alteration future researchers should consider is the use of an individualized asymmetry threshold formula when evaluating a participant. García-García et al found that the use of a specific asymmetry threshold formula classified more players as asymmetrical than with a fixed threshold as used in the current study [60]. Finally, the current study makes the assumption that asymmetry is abnormal within the examined population.…”
Section: Limitationsmentioning
confidence: 65%
“…Another alteration future researchers should consider is the use of an individualized asymmetry threshold formula when evaluating a participant. García-García et al found that the use of a specific asymmetry threshold formula classified more players as asymmetrical than with a fixed threshold as used in the current study [60]. Finally, the current study makes the assumption that asymmetry is abnormal within the examined population.…”
Section: Limitationsmentioning
confidence: 65%
“…However, other investigators showed that LAM asymmetry also occurs in sports with symmetrical movements (Adams et al, 2022; Linek et al, 2020). While soccer is also classified as a symmetrical sport (DeLang et al, 2017), most soccer players are much more likely to overuse one (dominant) lower limb during motor tasks such as passing and shooting, leading to asymmetry (Garcia-Garcia et al, 2022). From this perspective, it is difficult to determine unambiguously whether a given sport may lead to asymmetries in LAM thickness or to know how to address those effects.…”
Section: Discussionmentioning
confidence: 99%
“…The morphology and physiology of each of the LAMs can therefore be important in the sportsperson’s achievement of a high level of performance (Tschuikane et al, 2017). Although one of the important elements in sports training for soccer players is the development of comparable abilities in the use of both lower limbs, most athletes present a dominant or preferred lower limb that is much more frequently used for passes and shots during training and match situations, promoting the need for an asymmetric LAM exercise (Garcia-Garcia et al, 2022). Additionally, soccer players positioned in the lateral pitch areas during the pitch are likely to use the dominant lower limb most often (Marcori et al, 2022).…”
Section: Introductionmentioning
confidence: 99%